An evolutionary algorithm for the one-dimensional cutting stock problem - Araujo, Silvio A. [UNESP]; Constantino, Ademir A.; Poldi, Kelly C. (Wiley-Blackwell, 2011)
This paper deals with the one-dimensional integer cutting stock problem, which consists of cutting a set of available objects in stock in order to produce ordered smaller items in such a way as to minimize the waste of material. The case in which there are various types of objects available in stock in limited quantities is studied. A new heuristic method based on the evolutionary algorithm concept is proposed to solve the problem. This heuristic is empirically analyzed by solving randomly generated instances and the results are compared with other methods from the literature.
Keywords: integer optimization; cutting stock problem; evolutionary algorithm